THE IMPACT OF THE ADDITIONAL CREDIT ON THE ECONOMIC GROWTH AND PERSONAL INCOME. IS IT ALWAYS POSITIVE? - Sylwester Kozak (Polityki Europejskie, Finanse i Marketing)
Before the financial crisis, most studies indicated a positive impact of the credit growth on economic development. The experience of recent years significantly changed this view. The paper presents results of the analysis on relationship between credit growth and the GDP growth and growth of personal income (GDP per capita) in 2004-2011. The test was based on a panel regression model using data from the World Bank. It shows that the credit growth accelerates economic growth and personal income in countries with a moderate level of income. In case of high income euro countries, especially highly indebted economies credit growth is not favorable for the growth of GDP or GDP per capita, what could be explained by creation of the asset bubble and saturation of the economy with credit. In addition, dynamic of economic growth is mitigated by increasing inflation.